Asbestos‐like Pathogenicity of Long Carbon Nanotubes Alleviated by Chemical Functionalization1. Issue 8 (14th January 2013) - Ali‐Boucetta, Hanene; Nunes, Antonio; Sainz, Raquel; Herrero, M. Antonia; Tian, Bowen; Prato, Maurizio; Bianco, Alberto; Kostarelos, Kostas
<x xml:space="preserve">Abstract</x> Sometimes shorter is better: The apparent similarity between multi‐walled carbon nanotubes (MWNTs) and asbestos fibers has generated serious concerns about their safety profile. The asbestos‐like pathogenicity observed for long, pristine nanotubes (NTlong, see scheme) can be completely alleviated if their effective length is decreased as a result of chemical functionalization, such as with tri(ethylene glycol) (TEG).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>